Altered Expression of Genes Implicated in Xylan Biosynthesis Affects Penetration Resistance against Powdery Mildew - Chowdhury, Jamil; Lück, Stefanie; Rajaraman, Jeyaraman; Douchkov, Dimitar; Shirley, Neil J.; Schwerdt, Julian G.; Schweizer, Patrick; Fincher, Geoffrey B.; Burton, Rachel A.; Little, Alan (Frontiers in Plant Science, 2017)
Heteroxylan has recently been identified as an important component of papillae, which are formed during powdery mildew infection of barley leaves. Deposition of heteroxylan near the sites of attempted fungal penetration in the epidermal cell wall is believed to enhance the physical resistance to the fungal penetration peg and hence to improve pre-invasion resistance. Several glycosyltransferase (GT) families are implicated in the assembly of heteroxylan in the plant cell wall, and are likely to work together in a multi-enzyme complex. Members of key GT families reported to be involved in heteroxylan biosynthesis are up-regulated in the epidermal layer of barley leaves during powdery mildew infection. Modulation of their expression leads to altered susceptibility levels, suggesting that these genes are important for penetration resistance. The highest level of resistance was achieved when a GT43 gene was co-expressed with a GT47 candidate gene, both of which have been predicted to be involved in xylan backbone biosynthesis. Altering the expression level of several candidate heteroxylan synthesis genes can significantly alter disease susceptibility. This is predicted to occur through changes in the amount and structure of heteroxylan in barley papillae.